2020
DOI: 10.1007/s10815-020-01955-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic endometritis and altered embryo implantation: a unified pathophysiological theory from a literature systematic review

Abstract: Purpose Chronic endometritis (CE) is a frequent hysteroscopic and histological finding which affects embryo transfer implantation during IVF-ICSI cycles. In particular, CE impairs proper decidualization and, subsequently, implantation. Although this correlation has been clearly clarified, a pathophysiological explanation assembling all the studies performed has not been elucidated yet. For this reason, we have structured a systematic review considering all the original articles that evaluated a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 89 publications
(135 reference statements)
0
66
0
6
Order By: Relevance
“…Third, Song et al (3) found a low percentage of women with CE signs at hysteroscopy in the treatment arm (25/59, 42.4%). Previous studies found a significant correlation between the disappearance of CE signs at hysteroscopy and improvement of the patients' reproductive outcome (5). In this respect, the number of women in whom a relation between disappearance of hysteroscopic signs and enhancement of fertility could be evaluated was too small for significant results (3) enrolled patients with heterogeneous characteristics (i.e., suffering from infertility, repeated implantation failure, recurrent miscarriage, abnormal uterine bleeding, or cervical incompetence), potentially leading to miscellaneous estimates of the reproductive outcomes.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Third, Song et al (3) found a low percentage of women with CE signs at hysteroscopy in the treatment arm (25/59, 42.4%). Previous studies found a significant correlation between the disappearance of CE signs at hysteroscopy and improvement of the patients' reproductive outcome (5). In this respect, the number of women in whom a relation between disappearance of hysteroscopic signs and enhancement of fertility could be evaluated was too small for significant results (3) enrolled patients with heterogeneous characteristics (i.e., suffering from infertility, repeated implantation failure, recurrent miscarriage, abnormal uterine bleeding, or cervical incompetence), potentially leading to miscellaneous estimates of the reproductive outcomes.…”
mentioning
confidence: 89%
“…During the last 2 decades, there has been growing interest in the study of endometrial pathologies and their reproductive implications. Chronic endometritis (CE), defined as the abnormal invasion of plasma cells within the endometrial stroma, has been one of the most investigated conditions (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
“…In addition, a large number of patients with implantation failure were potentially included in the patients treated with IVF [ 43 , 44 ]. Since it has been reported that CE is related to implantation failure [ 45 , 46 ], and because we hypothesized that the occurrence of EMT was related to implantation failure, IVF patients were targeted in the present study. However, the occurrence of the EMT may differ from that in patients who are not infertile.…”
Section: Discussionmentioning
confidence: 99%
“…Irregular bleeding, pelvic pain, or dyspareunia can be symptoms of CE; however, in most cases, patients with a CE remain asymptomatic. CE could further negatively impact reproduction by altering uterine contractility, vascularization, decidualization, and autophagy [ 86 ]. Still, the cut-off level of CD138 + PC within the endometrium remains unclear.…”
Section: Alloimmunitymentioning
confidence: 99%
“…While Kitaya et al found no difference in identifying CE during the menstrual cycle [ 88 ], some studies showed a higher prevalence of CE in the proliferative phase compared to the secretory phase [ 89 , 90 , 91 ]. The underlying pathophysiological mechanism is likely to be an inflammatory reaction, which leads to an altered cytokine secretion [ 86 , 92 ]. CD68 + macrophages, CD83 + DC, CD8 + T cells, FOXp3 + Tregs [ 93 ], as well as uNK have shown to be elevated in CE [ 26 ].…”
Section: Alloimmunitymentioning
confidence: 99%